2000
DOI: 10.1016/s0895-7061(00)01179-1
|View full text |Cite
|
Sign up to set email alerts
|

What is critical renal artery stenosis?: Implications for treatment

Abstract: Renovascular disease due to progressive atherosclerotic renal artery stenosis is being diagnosed with increasing frequency in the elderly. At what degree of renal artery stenosis should intervention be recommended is not clear. To answer this question, unilateral or bilateral activation of the renin-angiotensin system or its absence were detected by captopril-stimulated renal vein renin measurements in 49 hypertensive patients, aged 63 years, with normal or near-normal renal function (serum creatinine concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Studies using balloon occlusion in humans indicate that this process requires development of a gradient across the lesion such that distal pressures fall at least by 10-20% below aortic pressure 18. Such pressure differences correspond to translesional peak systolic gradients of 15-25 mm and develop only when the cross-sectional area of occlusion approaches 70-80% as illustrated in FIGURE 1 19. An important corollary of this observation is that vascular lesions that fail to generate such a gradient are unlikely to participate in renovascular hypertension and do not benefit from measures to open the vessel.…”
Section: Pathophysiology: Renovascular Hypertension and The Role Of Rmentioning
confidence: 99%
“…Studies using balloon occlusion in humans indicate that this process requires development of a gradient across the lesion such that distal pressures fall at least by 10-20% below aortic pressure 18. Such pressure differences correspond to translesional peak systolic gradients of 15-25 mm and develop only when the cross-sectional area of occlusion approaches 70-80% as illustrated in FIGURE 1 19. An important corollary of this observation is that vascular lesions that fail to generate such a gradient are unlikely to participate in renovascular hypertension and do not benefit from measures to open the vessel.…”
Section: Pathophysiology: Renovascular Hypertension and The Role Of Rmentioning
confidence: 99%
“…(FIGURE 2). Renal vein renin sampling confirms that clinically detectable lateralization of renin production appear to require 80% stenosis (13). Hence, even lesions that are estimated at 60–70% lumen obstruction by a clinical test, such as duplex ultrasonography, may be non-functional.…”
Section: Estimating the Severity Of Obstructive Vascular Lesionsmentioning
confidence: 53%
“…In dog studies, a reduction in renal blood flow and an increase in blood pressure was not observed until renal artery constriction exceeded 75% . In humans, renin secretion, as assessed by captopril‐stimulated renal vein renin secretion, was observed to be stimulated only in patients with >80% stenosis . Loss of tissue perfusion and cortical oxygenation was reported with a mean stenosis of 77% .…”
Section: Patients With Aras That Is Not Hemodynamically Significantmentioning
confidence: 98%